P119 Brain function and fatigue in patients with inflammatory bowel disease. (15th January 2020) - Thomann, A; Schmitgen, M; Kmuche, D; Griebe, M; Ebert, M; Wolf, R C; Reindl, W
Abstract: Background: Fatigue is common in patients with inflammatory bowel diseases (IBD). It occurs in up to 80% of patients with active disease, but also a considerable proportion of patients in remission, and significantly affects quality of life. The underlying mechanisms are still poorly understood, and it is still unclear which patients will suffer from fatigue even in luminally quiescent disease. Task-based brain functional studies have examined neural correlates of fatigueability and found changes in the orbitofrontal cortex (OFC), among other regions. To the best our knowledge, the relationship between brain function and fatigue in IBD has not been investigated. This study aimed to examine the association between fatigue and resting-state brain function in remitted IBD patients. Methods: We obtained resting-state-functional MRI (rs-fMRI) data from 45 IBD patients in stable remission without current steroid or biological therapy and 17 healthy controls (HCs). Fatigue was assessed with Würzburger Erschöpfungsinventar Multiple Sklerose (WEIMuS). Preprocessing of rs-fMRI-data and calculation of amplitude of low frequency fluctuations (ALFF) was performed using the Data Processing Assistant for rs-fMRI. The resulting individual maps were analysed via second-level SPM multiple regression models in patients and HC to test for correlations between ALFF data and WEIMuS scores. Age, gender and mean framewise displacement were included as covariates of no interest and results were displayed at p < 0.001 (peak level) with a threshold of spatial extent ( k ) according to the expected voxels per cluster estimated by SPM. Results: Fatigue scores did not differ significantly between patients and controls (mean WEIMuS-scores 17.9 (SD 13.9) vs. 12.3 (SD 16.5), p = .17). Proportions of participants with fatigue scores above the cutoff (>32P.) were nearly identical in patients and HC (8/45 vs. 3/17). In patients, fatigue scores correlated positively with ALFF in the right central operculum and negatively with ALFF in the left OFC and left cerebellum (all p < .001, Figure 1). Fatigue and ALFF in the left cerebellum were also found to correlate in HC. Conclusion: This study shows fatigue-associated changes in brain activity in several brain regions. The negative association between fatigue and ALFF in the left OFC of IBD patients was not seen in HC, indicating that reduced ALFF in the OFC may represent a neural correlate of IBD-related fatigue. The OFC is thought to be involved in decision-making, which is described to be impaired in many fatigued IBD patients. If the association between fatigue and brain function detected in our study is confirmed in longitudinal IBD studies, these regions could serve as biomarkers when targeting fatigue in IBD.